2022
DOI: 10.1002/ppul.25802
|View full text |Cite
|
Sign up to set email alerts
|

The return of RSV during the COVID‐19 pandemic

Abstract: Respiratory syncytial virus (RSV) hospitalizations practically disappeared in 2020. Now, with Southern Hemisphere 2021 winter behind us, RSV has returned. Despite it is difficult to weigh the impact of pandemic mitigation measures on common respiratory virus circulation, it appears that acute respiratory infections in children are returning to their usual epidemiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 5 publications
2
12
0
3
Order By: Relevance
“…However, when the data from the CDC were analyzed, we found an unchanged flu vaccine acceptance rate since the pandemic outbreak. A sudden uptrend in RSV during COVID-19 was previously reported, mostly from regional hospitals [ 17 , 31 ]. In contrast, our study comprehensively summarized statistics from a national database.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the data from the CDC were analyzed, we found an unchanged flu vaccine acceptance rate since the pandemic outbreak. A sudden uptrend in RSV during COVID-19 was previously reported, mostly from regional hospitals [ 17 , 31 ]. In contrast, our study comprehensively summarized statistics from a national database.…”
Section: Discussionmentioning
confidence: 99%
“…recently reported that, at the beginning of the COVID-19 pandemic, the usual winter 2020/2021 Respiratory Syncytial Virus (RSV) peak did not occur in Oxfordshire, UK, with an inter-seasonal rise several months later, 1 as described worldwide. 2 , 3 , 4 , 5 , 6 We previously described, in our French tertiary hospital, that the delayed RSV 2020/2021 outbreak involved less adults and was associated with more hospitalization, higher age of pediatric inpatients and milder median clinical phenotype than observed before the COVID-19 pandemic. 2 In France, severe public restrictions (national lockdown, curfew) ended in May-June 2021, but some measures have been maintained (universal masking policy in adults and children ≥6 years in healthcare settings, schools, public transportations and most indoor spaces, educational interventions for prevention of community and healthcare-associated respiratory infections).…”
mentioning
confidence: 91%
“…3,6 These findings are consistent with reports made in similar epidemiological conditions, which indicated an increase in prevalence after the return to school. 10,11 In Argentina, this was already reported among hospitalized patients in the winter of 2021, 12 although few studies have been conducted in outpatients.…”
Section: Discussionmentioning
confidence: 91%